Povo Wassu Cocal : terra, religiões e conflitos - Oliveira, Aldjane de (2017)
This research has as focus to analyze and to understand the relations and conviviality between the Evangelical Wassu and the Catholic-Ouricuri Wassu, considering the environments and situations generating of possible symbolic conflicts. In the present work, I present, initially, a retrospective of the history of the Wassu Cocal People, based on an analysis in the light of Anthropology, in order to situate the Wassu people within ethnology and history in Brazilian society. The conflicts in the Wassu Cocal people's daily life, usually subtle, silenced or expressed, are perceived in this research through opinions, positions, invitations or exclusions in the day-to-day activities of the community, based on the different religions practiced in it. I do not conceive them (the conflicts) only in the grossest sense of the word, when it would arrive at ways of fact, but in its bland form: symbolic conflict. I consider conflict environments particularly: predilections for participation in events outside indigenous lands, disputes for public office and leadership in the community itself or outside it, influence of evangelical ideologies within indigenous schools, as well as the practice or notion of healing between the evangelical Wassu and the Wassu practitioners of Ouricuri. In an attempt to improve the theoretical development and writing of this research, I use the terms Evangelical Wassu and Catholic-Ouricuri Wassu, the latter as a theoretical category to analyze the group of people who declare themselves Catholic but practice Ouricuri, fulfill the obligations and keep the secrets of the rituals and beliefs of the ancestors.